1974
DOI: 10.1017/s0021859600051261
|View full text |Cite
|
Sign up to set email alerts
|

The genetic control of erythrocyte reduced glutathione in Australian Merino sheep

Abstract: The genetic control of the level of reduced glutathione (GSH) in the erythrocytes of pure bred Australian Merino sheep has been investigated. The data suggest that the erythrocyte GSH levels are in part controlled by a single pair of autosomal alleles, the gene for GSH-high (OSH a ) being dominant.The data also suggest that the levels of erythrocyte GSH within the GSH-high and GSH-low types are the result of polygenic influences. Heritability estimates of 0-7 and 0-5 within the GSH-high type and 1-2 in the GSH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

1975
1975
1988
1988

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…The high heritability obtained could be clue to such genetic control: the presence and frequency of a major gene affects heritability which generally is high (SMITH and WEBB 1981). Although in Finnish Landrace and Merino the genetic control of GSH is well established, even if some controversy remains, the results obtained suggest both the evidence of a main single gene and incomplete dominance for this trait, as suggested by others (BOARD et al 1974;ATROSHI 1979).…”
Section: Blup Solutions For Sire Effectsmentioning
confidence: 57%
See 2 more Smart Citations
“…The high heritability obtained could be clue to such genetic control: the presence and frequency of a major gene affects heritability which generally is high (SMITH and WEBB 1981). Although in Finnish Landrace and Merino the genetic control of GSH is well established, even if some controversy remains, the results obtained suggest both the evidence of a main single gene and incomplete dominance for this trait, as suggested by others (BOARD et al 1974;ATROSHI 1979).…”
Section: Blup Solutions For Sire Effectsmentioning
confidence: 57%
“…In Merinos the inheritance of glutathione is not clear: TUCKER and KILGOUR (1972) stated that in Tasmanian Merinos the gene for low GSH levels is dominant to that for high levels while BOARD et al (1974), from an investigation on a large number of Australian Merinos, found that the GSH deficiency is controlled by an autosomal recessive gene as in Finnish Landrace. These different results are still unexplained.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other investigators (BOARD, ROBERTS and EVANS 1974;BOARD and AGAR 1983) assumed that different GSH levels result from cumulative activity of genes that are active at different sites in the GSH metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Sheep with lowered or 'deficient' concentrations of erythrocyte GSH have been reprted in a number of different breeds (Tucker & Kilgour, 1970;Agar et al, 1972b;Kalla et al, 1972). Investigations by Tucker & Kilgour (1970) and Board et al (1974) suggested that this trait is inherited as an autosomal recessive allele.…”
Section: Introductionmentioning
confidence: 99%